Michael Handelsman: crítico desde y hacia la mitad del mundo (Tributo) - Medina, Manuel F. (2019)
This article states that the book entitled Guayaquil y sus escritores. Un homenaje a algunos clásicos que no se van, published in 2017 by Michael Handelsman, shows the author’s effort to fight the academic colonialism enthroned by elitist intellectual circles. His analysis of Literature, literary magazines and essays on Ecuadorian authors, is developed within Kimberlé Crenshaw’s inter-sectionalist theoretical framework, which allows us to analyze institutions that exert control and power. This essay provides examples of four studies by Handelsman, where his intention of interweaving Ecuadorian Literature within the global scene of critics can be perceived, as well as his intention to promote recognition of the aesthetic value of works unknown due to exclusivist attitudes and poor strategies of editorial distribution.